Antimicrobial resistance, Extended-Spectrum β-Lactamase production and virulence genes in Salmonella enterica and Escherichia coli isolates from estuarine environment. - Saharuetai Jeamsripong; Mullika Kuldee; Varangkana Thaotumpitak; Rungtip Chuanchuen (PLoS ONE, 2023)
The impact of antimicrobial resistance (AMR) on global public health has been widely documented. AMR in the environment poses a serious threat to both human and animal health but is frequently overlooked. This study aimed to characterize the association between phenotype and genotype of AMR, virulence genes and Extended-Spectrum β-Lactamase (ESBL) production from estuarine environment. The Salmonella (n = 126) and E. coli (n = 409) were isolated from oysters and estuarine water in Thailand. The isolates of Salmonella (96.9%) and E. coli (91.4%) showed resistance to at least one antimicrobial agent. Multidrug resistance (MDR) was 40.1% of Salmonella and 23.0% of E. coli. Resistance to sulfamethoxazole was most common in Salmonella (95.2%) and E. coli (77.8%). The common resistance genes found in Salmonella were sul3 (14.3%), followed by blaTEM (11.9%), and cmlA (11.9%), while most E. coli were blaTEM (31.5%) and tetA (25.4%). The ESBL production was detected in Salmonella (1.6%, n = 2) of which one isolate was positive to blaTEM-1. Eight E. coli isolates (2.0%) were ESBL producers, of which three isolates carried blaCTX-M-55 and one isolate was blaTEM-1. Predominant virulence genes identified in Salmonella were invA (77.0%), stn (77.0%), and fimA (69.0%), while those in E. coli isolates were stx1 (17.8%), lt (11.7%), and stx2 (1.2%). Logistic regression models showed the statistical association between resistance phenotype, virulence genes and ESBL production (p < 0.05). The findings highlighted that estuarine environment were potential hotspots of resistance. One Health should be implemented to prevent AMR bacteria spreading.